Overexpression of long noncoding RNA ANRIL inhibits phenotypic switching of vascular smooth muscle cells to prevent atherosclerotic plaque development in vivo - Hu, Da-Jun (Aging (Albany NY), 2020)
Background: Phenotypic switching of vascular smooth muscle cells (VSMCs) plays a key role in atherosclerosis. Long noncoding RNA ANRIL (lncRNA-ANRIL) is critical in vascular homeostasis. Metformin produces multiple beneficial effects in atherosclerosis. However, the underlying mechanisms need to be elucidated. Methods and Results: Metformin increased lncRNA-ANRIL expression and AMPK activity in cultured VSMCs, and inhibited the phenotypic switching of VSMCs to the synthetic phenotype induced by platelet-derived growth factor (PDGF). Overexpression of lncRNA-ANRIL inhibited phenotypic switching and reversed the reduction of AMPK activity in PDGF-treated VSMCs. While, gene knockdown of lncRNA-ANRIL by adenovirus or silence of AMPKγ through siRNA abolished AMPK activation induced by metformin in VSMCs. RNA-immunoprecipitation analysis indicated that the affinity of lncRNA-ANRIL to AMPKγ subunit was increased by metformin. In vivo, administration of metformin increased the levels of lncRNA-ANRIL, suppressed VSMC phenotypic switching, and prevented the development of atherosclerotic plaque in Apoe(-/-) mice fed with western diet. These protective effects of metformin were abolished by infecting Apoe(-/-) mice with adenovirus expressing lncRNA-ANRIL shRNA. The levels of AMPK phosphorylation, AMPK activity, and lncRNA-ANRIL expression were decreased in human atherosclerotic lesions. Conclusion: Metformin activates AMPK to suppress the formation of atherosclerotic plaque through upregulation of lncRNA-ANRIL.